ANALISIS KEBIJAKAN IMPLEMENTASI BRT (BUS RAPID TRANSIT) PEMERINTAH KOTA MEDAN DALAM MENGATASI KEMACETAN LALU LINTAS DI KOTA MEDAN - Emi Suryati, Christina; Revida, Erika; Maykel Siregar, Epafras (STKIP PGRI Situbondo, 2025)
The purpose of this study is to analyze the implementation policy of BRT (Bus Rapid Transit) of Medan City Government in overcoming traffic congestion in Medan City. This type of research is qualitative. Primary and secondary data were used as the data sources. The primary data were based on interview results. Secondary data uses figures and data, books and scientific journals which are used as the basis for scientific literature. The data analysis technique uses thematic analysis. The BRT policy in Medan City has great potential to overcome traffic congestion and improve public transportation systems. However, the success of the implementation is highly dependent on infrastructure improvements, increased coordination between agencies, and public awareness of the importance of switching to more efficient and environmentally friendly public transportation. In the analysis of the driving factors for the success of the role of actors in the implementation of the Bus Rapid Transit (BRT) policy in Medan City in overcoming traffic congestion in Medan City, the driving factors for the success of the role of the Medan City Government consist of very wide accessibility, qualified resources consisting of Financial Resources, Human Resources and Partnership Resources, and having a communicative coordination system